2022
DOI: 10.3390/biology11121848
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Magnetic Resonance Findings in Patients Recovered from COVID-19 Pneumonia and Presenting with Persistent Cardiac Symptoms: The TRICITY-CMR Trial

Abstract: The prevalence and clinical consequences of coronavirus disease 2019 (COVID-19)-related non-ischemic cardiac injury are under investigation. The main purpose of this study was to determine the occurrence of non-ischemic cardiac injury using cardiac magnetic resonance (CMR) imaging in patients with persistent cardiac symptoms following recovery from COVID-19 pneumonia. We conducted a single-center, cross-sectional study. Between January 2021 and May 2021, we enrolled 121 patients with a recent COVID-19 infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…But no statistically significant difference regarding RVEF. It was in concordance with Wojtowicz et al [14] who reported statistically significant difference between the two groups of patients with and without Non-Ischemic Cardiac Injury regarding LVEF (57% vs 61%, P<.001), but no statistically significant difference regarding LVEDV and RVEF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…But no statistically significant difference regarding RVEF. It was in concordance with Wojtowicz et al [14] who reported statistically significant difference between the two groups of patients with and without Non-Ischemic Cardiac Injury regarding LVEF (57% vs 61%, P<.001), but no statistically significant difference regarding LVEDV and RVEF.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed statistically significant difference between both groups regarding level of Tn I as we found 11 (47%) patients with elevated Tn I in myocarditis group versus only 1 (3.7%) patient in the normal group. This was in line with Wojtowicz et al [14] who reported statistically significant difference between the two groups of patients with and without non-ischemic cardiac injury using CMR regarding Tn I level. In the current study, there was a statistically significant difference between both groups regarding ECG abnormality as we found 12 (52%) patients with ECG abnormality in myocarditis group versus only 1 (3.7%) patient in the normal group.…”
Section: Discussionsupporting
confidence: 91%
“…We found increases in the rates of diagnostic procedures and detected pathological changes in the cardiovascular system during the third year of the COVID-19 pandemic, which also may suggest a chronic course of this disease. Prospects for the wider use of MRI in diagnosing not only chronic cardiac but also chronic lung complications of COVID-19 require further exploration, considering that pilot data show MRI to be an accurate and informative imaging modality in this regard [ 12 , 32 , 33 , 34 , 35 , 36 ]. The CMR may be considered the most useful noninvasive test to detect myocarditis and can give detailed information in terms of myocardial structure and function [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found the increases in the rates of diagnostic procedures and detected pathological changes of cardiovascular system during the third year of COVID-19 pandemic, which also may suggest chronic course of this disease. Prospects for wider use of MRI in diagnosing not only chronic cardiac, but also chronic lung complications of COVID-19 require further exploration considering that pilot data show MRI an accurate and informative imaging modality in this regard [12,[31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%